Factors Influencing the Effectiveness of the Online Patient Registration System at Maria Regina Hospital, Kotabumi, North Lampung - Rahmani, Alef Adlia; Paramarta, Vip; Syahidin, Rukhiyat (LP2M IAIN Palopo, 2026)
This study aims to analyze the factors influencing the effectiveness of the online patient registration system at Maria Regina Hospital, Kotabumi, North Lampung. A quantitative survey design was employed, with 95 respondents selected via purposive sampling from a population of 1,800 patients. Data were collected using Likert-scale questionnaires and analyzed through multiple linear regression following conversion to interval scale via the Method of Successive Intervals (MSI). Results indicate that patient digital literacy (X1), hospital technology infrastructure (X2), and system usage guidelines (X3) simultaneously and partially exert a significant effect on the effectiveness of the online registration system (Y). The regression equation is Y = 18.795 + 0.392X1 + 0.384X2 + 0.410X3. The coefficient of determination R² = .681, indicating that 68.1% of the variation in system effectiveness is explained by the three independent variables. The F-test confirms F(3, 91) = 6.511, p < .05, validating the overall model. These findings imply that hospitals must pursue an integrated strategy encompassing digital literacy programs for patients, strengthened technology infrastructure, and improved user guidance to maximize the effectiveness of online registration and enhance the overall quality of healthcare services.